Retrospective review of methodological foundations for the new monograph «Spectrometry in the near infrared regioN» - O. V. Soboleva; T. E. Elizarova; A. Yu. Arik; A. M. Koldina; M. A. Morozova (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The new pharmacopoeial monograph «Spectrometry in the near infrared region» reflects the results of a difficult path traversed from the development of measurement and analytical techniques to the introduction of NIR spectroscopy in the practice of quality control. This review discusses the new monograph of the XIII edition of the State Pharmacopoeia in the light of existing methodological approaches developed and validated for the assessment of drug quality parameters such as identification, content uniformity, assay, etc. Special attention is paid to the formation of spectral libraries - the factor of the sample’s «age» is considered as a source of additional spectral variability. The review raises the question of the NIR spectra identity criteria. Drawing on the example of techniques developed for the evaluation of batch variability (23 medicines) it was showed that obtained values of spectral range serve as unique characteristics of each individual product and production process, defining interlot reproducibility - the less the spectral distance between the series is, the more homogeneous the products are. NIR spectroscopy was shown to be effective for quantitative analysis of solid dosage forms and liquid substances. The authors considered the principles of operation as well as prospects for the practical use of the new technology - NIR chemical imaging, combining spectral analysis and digital image.